Gabapentin Add-On Therapy for Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The efficacy and safety of gabapentin (GBP) as add-on therapy in 237 children, aged 3 to 12 years, with refractory partial seizures were studied at the Alder Hey Children's Hospital, Liverpool, UK.